Subgrouping Poor Readers on the Basis of Individual Differences in Reading-Related Abilities - Catts, Hugh W. (2003)
The present study investigated the use of the Reading Component Model to subgroup poor readers. A large sample of poor readers was identified in second grade and subgrouped on the basis of relative strengths and weaknesses in word recognition and listening comprehension. Although homogeneous subgroups were not identified, poor readers could be classified into four subgroups that differed significantly in reading-related abilities. Further analyses showed that poor readers' strengths and weaknesses in listening comprehension, and to a lesser extent in word recognition, were foreshadowed by their abilities on related kindergarten measures. Follow-up testing in the fourth grade indicated that poor readers' individual differences in word recognition and listening comprehension were consistent and that subgroups were moderately stable. The implications of these results for the assessment and remediation of reading disabilities are discussed.